ORGANIZATION OF ACCOUNTING IN STRUCTURES OF A SMALL BUSINESS IN THE CONSTRUCTION FIELD - Akbarjon Isomuhamedov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article examines the issues of effective organization of accounting in small business entities operating in the construction industry, methods of cost determination, and the use of accounting information in the preparation of cost estimates.